Implementation of Technology-Based Learning Media in Javanese Language Learning Phase F - Ociana, Sabrina Zalfa; Yuwono, Agus (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to describe the ”Implementation of Technology-Based Learning Media in Javanese Language Learning Phase F students”. It also identifies the problems encountered during implementation and the solutions applied to overcome them. The research is motivated by the need for adaptable learning in response to technological advancements, particularly within the Javanese local content curriculum, which students often find unengaging. We adopted a descriptive qualitative approach with a case study research design. The study was conducted at SMA Negeri 1 and SMA Negeri 2 Purbalingga, involving teachers, students, and school principals as subjects. Data collection techniques included direct observation of the learning process, in-depth interviews with various stakeholders, and documentation of learning tools and media. The findings indicate that technology-based press, such as PowerPoint (PPT), learning videos, and interactive applications like Quizizz, Kahoot, and Canva, significantly enhanced student participation and comprehension. The primary obstacles to implementing these media included limited internet access, low digital literacy among teachers, and uneven distribution of infrastructure. Solutions implemented to address these issues involved teacher training, providing offline media, and improving school technology infrastructure. This research highlights the importance of integrating technology into local content learning, which should be grounded in cultural wisdom and contemporary needs.